Part Whole Part and Whole Part Whole Affect Volley Normal Smash Ability - Anggara, Harini (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2018)
The purpose of this research is to examine the different impact of part whole part and whole part whole practice method, examine the different normal smash skill toward leg muscle power and examine interaction impact of practice method and leg muscle power toward normal smash skill to volleyball achievement development student. This research is experimental research that means to compare two different treatments on research subject. Thirty two samples use probability sampling. Independent variable is part whole part and whole part whole practice method. Attributive variable is high leg muscle power and low leg muscle power. Dependent variable is volleyball smash skill. Data collection technique in this research use pretest and posttest. Treatment undergoes through 18 meeting. Data analysis technique that used is Varian analysis (AVANA). The result of this result shows that in student group that given whole part whole practice method has better result than student group that given part whole part treatment (104,37 > 81,75) toward volleyball smash result. In student group that having high leg muscle power has better result compared with student group that having low leg muscle power (112,31> 70,87) toward volleyball smash result. There is interaction between practice method and leg muscle power toward volleyball smash result.